KOMPOSISI FITOPLANKTON YANG DITEMUKAN DI DANAU DIATAS KABUPATEN SOLOK - Muhammad Yahya; Rina Widiana; Renny Risdawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Lake Diatas in Solok Regency has experienced increasing tourism, agricultural, and aquaculture activities that may affect water quality. This study aimed to analyze the composition of phytoplankton as a bioindicator of water quality. A descriptive survey method with purposive random sampling was applied at six stations (September–December 2025). Samples were collected using a plankton net, preserved with 4% formalin, and identified to the genus level. Analyses included density, relative density, frequency, relative frequency, and the Shannon–Wiener diversity index (H’), supported by measurements of temperature, pH, and dissolved oxygen (DO). Fifteen genera from four classes were identified, with Ceratium as the dominant genus. The H’ value ranges from 2.219 – 2.3968 indicating oligotrophic conditions (light pollution).